The Construction of Rider Community Identity In Yamaha Indonesia’s Tiktok Content - Aden Bagus; Khaerudin Imawan (Indonesian Journal Publisher, 2026)
The rise of social media, particularly TikTok, has prompted brands to act not only as producers but also as key players in shaping community identity. The research problem in this study arises from the scarcity of research examining how the identity of the rider community is constructed by automotive brands through short-form video content on TikTok. This study aims to analyze the construction of rider community identity built by the TikTok account @yamahaindonesia through linguistic, visual, and symbolic representations, as well as how that identity is interpreted by the audience. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation of Yamaha Indonesia’s TikTok content from November 2025 and in-depth interviews with three informants who are Yamaha riders and TikTok users. Data analysis was conducted using semiotic analysis of representation. The results indicate that Yamaha constructs the identity of the rider community as a cohesive, modern, and community-oriented group through the use of casual language, visuals of group riding, and consistent brand symbols. However, this identity construction still reflects a negotiation between community interests and brand promotional interests. This study concludes that TikTok functions as a strategic space for symbolically framing the identity of the rider community, however, it is recommended that the brand engage the community in a more participatory manner to strengthen long-term loyalty